A novel scavenger receptor 5-based antibiotic-independent selection method for generation of stable recombinant protein-producing mammalian cell lines especially suitable for proteins affecting cell adhesion. (October 2012) - Ojala, Juha Risto Matias; Pikkarainen, Timo; Domogatskaya, Anna; Tryggvason, Karl; Rodin, Sergey
The establishment of stable recombinant protein-producing mammalian cell lines is an expensive, time-consuming, tedious procedure. In some cases, expressed recombinant proteins have adverse effects on host cell function, including cell adhesion. Based on the adhesive properties of SCARA5, a scavenger receptor (SR) of the class A SR family, we developed a method for selection of stable recombinant protein-producing cell clones that relies on an internal ribosome entry site (IRES) vector where the protein of interest is expressed in the same messenger RNA as SCARA5, resulting in improved adhesion and increased cell viability of recombinant protein-producing cells in serum-free media. This method does not depend on antibiotics, complicated selective cell culture media or equipment, and thus offers the advantages of being inexpensive, environmentally friendly, and simple.